2023
DOI: 10.1037/pspp0000422
|View full text |Cite
|
Sign up to set email alerts
|

Well-being in social interactions: Examining personality-situation dynamics in face-to-face and computer-mediated communication.

Abstract: Decades of research show that people's social lives are linked to their well-being. Yet, research on the relationship between social interactions and well-being has been largely inconclusive with regard to the effects of person-situation interactions, such as the interplay between contextual factors (e.g., interactions occurring in physical vs. digital contexts, different interaction partners) and dispositional tendencies (e.g., Big Five personality traits). Here, we report on exploratory and confirmatory find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 125 publications
7
46
1
Order By: Relevance
“…First, as discussed above, effects may reside at shorter timescales. However, this explanation is contradicted by studies similarly finding few crosslevel interactions in everyday life (e.g., social interactions: Kroencke et al, 2022;Sun et al, 2020; situation-state dynamics more generally: Kuper et al, 2022;Sherman et al, 2015;Wilt & Revelle, 2019).…”
Section: Cross-level Interactionsmentioning
confidence: 83%
See 1 more Smart Citation
“…First, as discussed above, effects may reside at shorter timescales. However, this explanation is contradicted by studies similarly finding few crosslevel interactions in everyday life (e.g., social interactions: Kroencke et al, 2022;Sun et al, 2020; situation-state dynamics more generally: Kuper et al, 2022;Sherman et al, 2015;Wilt & Revelle, 2019).…”
Section: Cross-level Interactionsmentioning
confidence: 83%
“…Many of the associations are in line with the existing literature. For instance, previous work has similarly found positive between-person associations between well-being and exercise (Buecker et al, 2021;Kroencke et al, 2019;Wiese et al, 2018), social activities (e.g., Kroencke et al, 2022;Lucas et al, 2008;Sun et al, 2020), holidays (Nawijn & Veenhoven, 2011), and cultural activities (e.g., Schulz et al, 2018). Moreover, these findings are broadly in line with the suggestion that active leisure activities (e.g., exercise, social activities) are more positively linked to well-being than passive leisure activities (e.g., watching TV; see also Holder et al, 2009).…”
Section: Between-person Associationsmentioning
confidence: 96%
“…In addition to studies investigating different leisure activities simultaneously, large literatures exist about specific activities. For instance, more frequent social interactions have been associated with higher well-being (e.g., Lucas et al, 2008;Kroencke et al, 2022;Sun et al, 2020). Similarly, physical activity is positively associated with well-being between persons (e.g., Buecker et al, 2021;Kroencke et al, 2019;Wiese et al, 2018).…”
Section: Between-person Associationsmentioning
confidence: 99%
“…Other work has focused on specific leisure activities at the within person level. For instance, many studies indicate momentary well-being benefits of social interactions (e.g., Kroencke et al, 2022;Sun et al, 2020) and positive effects of social leisure on life satisfaction were also reported at larger timescales (e.g., Becchetti et al, 2012). Physical activity has been related to momentary (Liao et al, 2015), weekly (e.g., Kroencke et al, 2019), and biennial fluctuations in well-being (Perales et al, 2014), and similar effects were PERSONALITY, LEISURE ACTIVITIES, AND WELL-BEING evident in experimental designs (Buecker et al, 2021).…”
Section: Within-person Associationsmentioning
confidence: 99%
See 1 more Smart Citation